The photocatalytic H2O2 production by metal-free photocatalysts under visible-light irradiation - Xu, Xiahong; Sui, Yan; Chen, Wentong; Huang, Wei; Li, Xiaodan; Li, Yuntong; Liu, Dongsheng; Gao, Shuang; Wu, Wenxin; Pan, Changwang; Zhong, Hong; Wen, He-Rui; et al. (Applied catalysis. B, Environmental, 2024)
The photocatalytic H2O2 production from H2O and O2 over organic polymers is a promising approach to achieve solar-to-chemical energy conversion. The continuous efforts have led to rapid development of various metal-free-based photocatalysts for specific H2O2 production, but generalizations and summarization are obviously inadequate. This review mainly focuses on the state-of-the-art development process of metal-free-based photocatalysts for photocatalytic H2O2 production via combining O2 reduction and H2O oxidation reactions under visible light irradiation. The representative research work on photocatalytic H2O2 production by various metal-free-based photocatalytic systems, including graphite carbon nitride (g-C3N4), covalent organic frameworks (COFs), covalent triazine frameworks (CTFs) and covalent organic polymers (COPs) was highlighted. The strategies for structure and property optimization of metal-free-based photocatalysts at molecular-level have been proposed for improving the photocatalytic performance. The challenges and future directions have also been provided to guide the design and synthesis of metal-free-based photocatalytic system. [Display omitted] •The state-of-the-art development of photocatalytic H2O2 production by metal-free photocatalysts was summarized.•Successful strategies to maximize the catalytic performance were assessed.•Representative research works on photocatalytic H2O2 production was highlighted.•Challenges and future directions discussed in the end.